Antimicrobial capping agents on silver nanoparticles made via green method using natural products from banana plant waste - Jimmy K. Kabeya; Nadège K. Ngombe; Paulin K. Mutwale; Justin B. Safari; Gauta Gold Matlou; Rui W.M. Krause; Christian I. Nkanga (Artificial Cells, Nanomedicine, and Biotechnology)
Herein, we investigated the phytochemical composition and antibacterial activities of the organic layers from biosynthesized silver nanoparticles (AgNPs). AgNPs were synthesized using Musa paradisiaca and Musa sapientum extracts. UV-vis absorption in the 400–450 nm range indicated surface plasmonic resonance peak of AgNPs. Samples analyses using dynamic light scattering and transmission electron microscopy revealed the presence of particles within nanometric ranges, with sizes of 30–140 nm and 8–40 nm, respectively. Fourier transform infrared (FTIR) unveiled the presence of several organic functional groups on the surface of AgNPs, indicating the presence of phytochemicals from plant extracts. Thin layer chromatography (TLC) of the phytochemicals (capping agents) from AgNPs identified multiple groups of secondary metabolites. These phytochemical capping agents exhibited antibacterial activities against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, with minimum inhibitory concentrations ranging from 62.5 to 1000 µg/mL. Regardless of the bacterial species or plant parts (leaves or pseudo-stems), capping agents from M. sapientum nanoparticles displayed significantly enhanced antibacterial effectiveness compared to all other samples, including the raw plant extracts and biosynthesized capped and uncapped AgNPs. These results suggest the presence of antimicrobial phytochemicals on biosynthesized AgNPs, highlighting the promise of green nanoparticle synthesis as a valuable approach in bioprospecting antimicrobial agents.